Perceived Expressed Emotion in the Illness Narratives of Individuals with Chronic Gastrointestinal Disorders - Pastryk, Tetiana; Kireieva, Zoia; Kordunova, Nataliia; Lyla, Mahdalyna (East European Journal of Psycholinguistics, 2021)
While expressed emotion has long been considered a valid predictor of a poor clinical outcome in individuals with mental and physical conditions, the present study marks the empirical investigation to assess specific communication patterns between family members and individuals with chronic gastrointestinal disorders. Following a rich tradition of studying illness narratives and a narrative approach to healing chronic illnesses, the present study examined illness narratives in a group of 40 mid-life adults with chronic gastrointestinal disorders. Two reliable, independent experts unfamiliar with the participants’ research objectives and diagnostic status coded all narratives (ICC = .77). Self-narratives describing the illness and its impact on the family life were analyzed for a set of narrative elements, including agency, communion fulfilment, and narrative coherence. In addition, the study applies measures to assess expressed emotion, criticism towards family and perceived criticism towards individuals with a condition. The correlation analysis results indicate an association between agency and criticism (.33) and perceived criticism (.33). The main issue emerging from the multiple regression analysis findings is that agency of the narrative, criticism towards family and duration of disease taken together contribute to perceived criticism of the family towards the individual with a condition. However, a family’s criticism towards the individual with a condition is the only independent significant predictor of perceived criticism. One of the more significant findings from this study is that substantial autonomy from significant others and empowerment of individuals with a condition could worsen the family environment and have an unfavourable clinical outcome. More practical information on service users’ autonomy and its impact on disease self-management would help us establish a greater accuracy.